Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Enhancing Fifth Graders’ Awareness of Syntactic Features in Mathematical Word Problems: A Design Research Study on the Variation Principle - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik, 41(2))

Symmetry in optimal control: A multiobjective model predictive control approach - Flaßkamp, K.; Ober-Blöbaum, Sina; Peitz, S. (Advances in Dynamics, Optimization and Computation)

Expertise von Lehrpersonen für inklusiven Mathematikunterricht der Sekundarstufe - Ausgangspunkte zur Professionalisierungsforschung. - Seitz, Susanne; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (K:ON Kölner Online-Journal für Lehrer*innenbildung)

Verstehensgrundlagen diagnostizieren - Welche Wissenselemente fokussieren Lehrkräfte? - Dröse, Jennifer (Beiträge zum Mathematikunterricht 2020)

Textaufgaben lesen lernen – eine digital gestützte Einheit mit App - Dröse, Jennifer; Eisen, V.; Prediger, Susanne; Altieri, M.; Schellenbach, M.; Menning, R. (Mathematik lehren 223)

The Approximation of Invariant Sets in Infinite Dimensional Dynamical Systems - Gerlach, Raphael; Ziessler, Adrian (Advances in Dynamics, Optimization and Computation)
In this work we review the novel framework for the computation of finite dimensional invariant sets of infinite dimensional dynamical systems developed in [6] and [36]. By utilizing results on embedding techniques for infinite dimensional systems we extend a classical subdivision scheme [8] as well as a continuation algorithm [7] for the computation of attractors and invariant manifolds of finite dimensional systems to the infinite dimensional case. We show how to implement this approach for the analysis of delay differential equations and partial differential equations and illustrate the feasibility of our implementation by computing the attractor of the Mackey-Glass equation and the unstable manifold of the one-dimensional Kuramoto-Sivashinsky equation.

On the equivariance properties of self-adjoint matrices - Dellnitz, Michael; Gebken, Bennet; Gerlach, Raphael; Klus, Stefan (Dynamical Systems)
We investigate self-adjoint matrices A∈Rn,n with respect to their equivariance properties. We show in particular that a matrix is self-adjoint if and only if it is equivariant with respect to the action of a group Γ2(A)⊂O(n) which is isomorphic to ⊗nk=1Z2. If the self-adjoint matrix possesses multiple eigenvalues – this may, for instance, be induced by symmetry properties of an underlying dynamical system – then A is even equivariant with respect to the action of a group Γ(A)≃∏ki=1O(mi) where m1,…,mk are the multiplicities of the eigenvalues λ1,…,λk of A. We discuss implications of this result for equivariant bifurcation problems, and we briefly address further applications for the Procrustes problem, graph symmetries and Taylor expansions.

Spectral Properties of Convex Bodies - Hilgert, Joachim; Barnum, H. (J. of Lie Theory)

Mathematik studieren -- Ein Ratgeber für Erstsemester und solche, die es vielleicht werden wollen